Regulation of Cell Proliferation and Migration by TAK1 via Transcriptional Control of von Hippel-Lindau Tumor Suppressor - Tan, Siew Hwey (American Society for Biochemistry and Molecular Biology, 2009)
Skin maintenance and healing after wounding requires complex epithelial-mesenchymal interactions purportedly mediated by growth factors and cytokines. We show here that, for wound healing, transforming growth factor-β-activated kinase 1 (TAK1) in keratinocytes activates von Hippel-Lindau tumor suppressor expression, which in turn represses the expression of platelet-derived growth factor-B (PDGF-B), integrin β1, and integrin β5 via inhibition of the Sp1-mediated signaling pathway in the keratinocytes. The reduced production of PDGF-B leads to a paracrine-decreased expression of hepatocyte growth factor in the underlying fibroblasts. This TAK1 regulation of the double paracrine PDGF/hepatocyte growth factor signaling can regulate keratinocyte cell proliferation and is required for proper wound healing. Strikingly, TAK1 deficiency enhances cell migration. TAK1-deficient keratinocytes displayed lamellipodia formation with distinct microspike protrusion, associated with an elevated expression of integrins β1 and β5 and sustained activation of cdc42, Rac1, and RhoA. Our findings provide evidence for a novel homeostatic control of keratinocyte proliferation and migration mediated via TAK1 regulation of von Hippel-Lindau tumor suppressor. Dysfunctional regulation of TAK1 may contribute to the pathology of non-healing chronic inflammatory wounds and psoriasis.